2023
DOI: 10.31181/dmame712024895
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a Multi-Objective Optimization Model for Engineering Projects Based on NSGA-II Algorithm under the Background of Green Construction

Fushun Zhang

Abstract: In the context of Sustainability Development (SD), Green Construction (GC) has become a key direction for optimizing engineering project objectives. In order to improve the management ability of project engineering in GC, an improved NSGA - II algorithm was used in this study to establish a multi-optimization model for engineering projects. In this process, the hill climbing is introduced to improve the search ability of NSGA - Ⅱ algorithm. Finally, a Multi-Objective Optimization (MOP) model with strong conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In a survey conducted on the use of multi-objective algorithms in construction project management during the period 2012-2016, Alothaimeen and Arditi [47] reported that NSGA-II was the most commonly used algorithm. Recent applications of NSGA-II in project management included sustainability development, green construction, and carbon emissions as optimization objectives [48,49]. In NSGA-II, fitness is assigned according to a two-level criteria, the first depends on the dominance rank of the individuals, whereas the second is assigned considering the crowding distance of the individuals of the same dominance rank.…”
Section: Nsga-iimentioning
confidence: 99%
“…In a survey conducted on the use of multi-objective algorithms in construction project management during the period 2012-2016, Alothaimeen and Arditi [47] reported that NSGA-II was the most commonly used algorithm. Recent applications of NSGA-II in project management included sustainability development, green construction, and carbon emissions as optimization objectives [48,49]. In NSGA-II, fitness is assigned according to a two-level criteria, the first depends on the dominance rank of the individuals, whereas the second is assigned considering the crowding distance of the individuals of the same dominance rank.…”
Section: Nsga-iimentioning
confidence: 99%